STRATEGI PENINGKATAN OMSET PENJUALAN BAGI PEDAGANG PASAR BULU SETELAH RENOVASI - Emaya Kurniawati; Wyati Saddewisasi; Sri Yuni USM Semarang Widowati (Adbis: Jurnal Administrasi dan Bisnis, 2020)
The purpose of this research is to find solutions and determine the strategies of Fur Market traders in order to increase their sales turnover. The methodology of this research is the method of solving problems using qualitative descriptive and SWOT analysis by making direct observations or observations, interviews and documentation. The results of the SWOT analysis of traders at the Semarang Fur Market are in a growth strategy which is designed to achieve growth in sales, capital or profits or a combination of the three. Where must maintain the strengths and opportunities that exist and minimize the threats and weaknesses that have Fur Market traders